1997
DOI: 10.1073/pnas.94.26.14559
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporally controlled site-specific somatic mutagenesis in the mouse

Abstract: The efficient introduction of somatic mutations in a given gene, at a given time, in a specific cell type will facilitate studies of gene function and the generation of animal models for human diseases. We have shown previously that conditional recombination-excision between two loxP sites can be achieved in mice by using the Cre recombinase fused to a mutated ligand binding domain of the human estrogen receptor (Cre-ER T ), which binds tamoxifen but not estrogens. DNA excision was induced in a number of tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(150 citation statements)
references
References 17 publications
6
142
0
Order By: Relevance
“…The R26R reporter has thus far proven to be an ideal reporter because of its expression in embryonic and adult cells, including those of the central and peripheral nervous systems, limb, skin, lung, and heart. A significant advance in genetic fate mapping has been the introduction of inducible forms of Cre in mice to accurately control when cells are marked (Brocard et al, 1997;Kimmel et al, 2000;Zirlinger et al, 2002;Guo et al, 2003;Ahn and Joyner, 2004;Harfe et al, 2004;Zervas et al, 2004). We have termed such an approach Genetic Inducible Fate Mapping, or GIFM (Fig.…”
Section: Genetic Fate Mapping In Mouse: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The R26R reporter has thus far proven to be an ideal reporter because of its expression in embryonic and adult cells, including those of the central and peripheral nervous systems, limb, skin, lung, and heart. A significant advance in genetic fate mapping has been the introduction of inducible forms of Cre in mice to accurately control when cells are marked (Brocard et al, 1997;Kimmel et al, 2000;Zirlinger et al, 2002;Guo et al, 2003;Ahn and Joyner, 2004;Harfe et al, 2004;Zervas et al, 2004). We have termed such an approach Genetic Inducible Fate Mapping, or GIFM (Fig.…”
Section: Genetic Fate Mapping In Mouse: An Overviewmentioning
confidence: 99%
“…1). The most common strategy for temporally regulating Cre activity has been to generate Cre fusion proteins with a tamoxifen-responsive Estrogen Receptor ligand binding domain from the human (ER T , Feil et al, 1996 andBrocard et al, 1997;ER T2 , Feil et al, 1997) or mouse (ER TM , Hayashi and McMahon, 2002) gene. CreER is sequestered in the cytoplasm by heat shock protein 90 (Hsp 90).…”
Section: Genetic Fate Mapping In Mouse: An Overviewmentioning
confidence: 99%
“…Tamoxifen-regulated CreER T transgenic lines (Feil et al, 1996;Brocard et al, 1997;Vooijs et al, 2001;Hayashi and McMahon, 2002; reviewed by Nagy, 2000) offer versatile tools to dissect the different functions of genes that play critical roles at multiple stages of development and postnatally and, thus, have the potential to greatly increase our understanding of the regulation of tissues and cell types that form over a broad developmental time range. They have also proven to be very powerful tools for lineage and fate mapping studies in mice (e.g., Kimmel et al, 2000;Harfe et al, 2004;Ahn and Joyner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The first brand of inducible Cre recombinases employs a truncated progesterone receptor which is directly fused to the Cre recombinase (96,157), whereas the second approach makes use of a fusion between the Cre recombinase and an estrogen receptor (48, 93, 94, 116, 124, 127). Nevertheless, close inspection of the induced recombination frequencies clearly demonstrated that recombination mediated by some first-generation fusion-recombinases might be mosaic depending very much on the tissue type (13,24,67,124,143,145). It is therefore to be assumed that better inducible recombinase molecules are needed to efficiently regulate Cre or Flp activity in the mouse (57,59,85,157).…”
Section: Conditional Gene Targetingmentioning
confidence: 99%